2021
DOI: 10.1111/aor.13922
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extracorporeal membrane oxygenation in adults with active hematologic and nonhematologic malignancy

Abstract: Although the number of cancer patients admitted to the intensive care unit is increasing, the data on the use of extracorporeal membrane oxygenation in patients with malignancy are limited. We applied extracorporeal membrane oxygenation to carefully selected patients with active hematologic malignancy or nonhematologic malignancy who experienced respiratory or cardiac failure despite maximal conventional therapy. Patients with active malignancy who underwent extracorporeal membrane oxygenation in our instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Admission due to ARF is associated with poor outcomes [ 112 , 113 , 114 ] and worsens if invasive mechanical ventilation is needed [ 115 , 116 ]. Nevertheless, efforts have been made in patients with hematologic malignancy to bridge ARF to recovery by use of ECMO [ 76 , 80 , 117 , 118 , 119 , 120 , 121 , 122 ]. All these trials conducted over a period of more than 10 years consistently demonstrated a high ICU and in-hospital mortality of more than 50% for patients treated with ECMO ( Table 6 ).…”
Section: Relative Contraindications To the Initiation Of Ecmomentioning
confidence: 99%
“…Admission due to ARF is associated with poor outcomes [ 112 , 113 , 114 ] and worsens if invasive mechanical ventilation is needed [ 115 , 116 ]. Nevertheless, efforts have been made in patients with hematologic malignancy to bridge ARF to recovery by use of ECMO [ 76 , 80 , 117 , 118 , 119 , 120 , 121 , 122 ]. All these trials conducted over a period of more than 10 years consistently demonstrated a high ICU and in-hospital mortality of more than 50% for patients treated with ECMO ( Table 6 ).…”
Section: Relative Contraindications To the Initiation Of Ecmomentioning
confidence: 99%
“…Subgroup analysis demonstrated that hematological malignancies had the lowest 6-month survival compared with other immunodeficiency severe ARDS patients and patients with solid tumor (P=0.02). In another study including 68 nonhematologic malignancy patients with respiratory or cardiac failure who received ECMO as salvage therapy despite conventional therapy, the 6-month survival was 26.5% (20).…”
Section: Question 3 Can Extracorporeal Membrane Oxygenation (Ecmo) Be Used In the Treatment Of Perioperative Severe/ Refractory Acute Resmentioning
confidence: 98%
“…Patients with hematologic malignancy patients had increased risk of bleeding compared with solid malignancies (44% versus 33%) [ 85 ]. Another study of patients with cancer treated with ECMO showed lower survival in-hospital (13% vs 38%) and 6-month survival (3% vs 26%) rates among patients with hematologic malignancies compared with solid tumors [ 86 ]. In a small, single-center study of 23 patients with hematologic malignancies on ECMO (14 on veno-arterial ECMO and 9 on VV-ECMO), there was a significant rate of in-hospital mortality with 91% of patients dying after a median ECMO duration of 105 h [ 87 ].…”
Section: Heart Failure Shock and Temporary Mechanical Circulatory Sup...mentioning
confidence: 99%